Economic Analysis of mixed grazing by sheep and goats in a semi-arid environment - Williams, Timothy O.; Fernández Rivera, S. (International Livestock Research Institute, 2004)
This paper demonstrates the usefulness and importance of an holistic approach in analysing complex production systems. It determines the optimum stocking rate and species mix that will maximise profit and compare this with the biological optimum stocking rate and species mix and; the effects of output price variation on the optimum stocking rate, species mix and maximum profit.